Selective metal recovery from printed circuit board wastewater - Md Ali, Abd Halim (2013)
Due to the high contain of metals in spent etching waste solution, the disposal of etching waste solution is an economic and ecological concern to electric and electronic manufacturer. This study has been initiated to investigate if metals ions can be recovered selectively in spent etching waste solution. The recovery process is expected to have an enhanced value if the recovered metal can be recycled and thus bring to the cost effective solution method. In the initial work, acid recovery by solvent extraction method was done in order to increase the pH of the solution to pH > 2. Three different volume ratio of TBP: HNO3 shows a significant value to extract nitric acid at a significant optimum experimental condition which is 50:50, 60:40 and 70:30. Based on the effectiveness of extraction versus the optimum usage of volume of TBP used, ratio of 50:50 has an advantage over the ratio of 70:30 in term of the optimisation usage of the overall volume to extract the nitric acid at its optimum condition. Six extraction stages are necessary to increase the pH of the aqueous solution by 50% TBP to pH >2. Electrochemical experiments were carried out and showed that that the deposition of metals on glassy carbon and graphite electrodes occurred at about the same potential voltage in between -0.60 V to -0.85 V. Based on scanning electron microscopy images, it can be seen that glassy carbon electrode is a suitable electrode material to recover copper at low potential voltage and graphite electrode work best to recover tin, lead and iron as an aggregate mixtures at higher potential voltage. However, selective recovery is not feasible in this work as the metals recovered formed as aggregates mixtures.